ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA SAHAM PADA PERUSAHAAN SEKTOR PERBANKAN DI BURSA EFEK INDONESIA - Angelina, Vivian; Tipa, Handra (SCIENTIA JOURNAL, 2022)
In general, banking companies always improves its companies performance to make it better so that every investors will not hesitate to invest in the company, which of course will affect the companies stock price. An investor who wants to invest must have a mature strategy and knowledge so that the investment can be profitable, such as analyzing company financial statements using several commonly used financial ratios. This research aims to analyze the effect of return on equity, earning per share and debt to equity ratio on stock prices in various banking companies listed in Indonesia Stock Exchange. The population in this study consisted of 46 companies and the study used techniques and samples in the form of purposive sampling and showed that the samples that could be used consisted of 39 companies multiplied by a period of 5 years. The results show that partially return on equity, earnings per share and debt to equity ratio have a negative and significant effect on stock prices. The F test states that simultaneously return on assets, loan to deposit ratio and debt to asset ratio return on equity, earnings per share and debt to equity ratio have a significant effect on stock prices. Keywords: stock price, return on equity, earning per share, debt to equity ratio.